2010
DOI: 10.3109/10253890.2010.512376
|View full text |Cite
|
Sign up to set email alerts
|

The vasopressin Avpr1b receptor: Molecular and pharmacological studies

Abstract: The distribution, pharmacology and function of the arginine vasopressin (Avp) 1b receptor subtype (Avpr1b) has proved more challenging to investigate compared to other members of the Avp receptor family. Avp is increasingly recognised as an important modulator of the hypothalamic-pituitary-adrenal (HPA) axis, an action mediated by the Avpr1b present on anterior pituitary corticotrophs. The Avpr1b is also expressed in some peripheral tissues including pancreas and adrenal, and in the hippocampus, paraventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 141 publications
(188 reference statements)
2
94
1
1
Order By: Relevance
“…In accordance with this notion, pretreatment with the selective V1b antagonist SSR149415 attenuated HPA activity during acute cocaine withdrawal. This result also suggests that the HPA activation was partially mediated through V1b receptors, which are expressed in the corticotropic ACTH-positive cells (Hernando et al, 2001), and modulate HPA axis activity in response to a variety of stressors (Roper et al, 2011) (see more discussion below).…”
Section: Avp Gene Expression In the Ppvnmentioning
confidence: 86%
See 1 more Smart Citation
“…In accordance with this notion, pretreatment with the selective V1b antagonist SSR149415 attenuated HPA activity during acute cocaine withdrawal. This result also suggests that the HPA activation was partially mediated through V1b receptors, which are expressed in the corticotropic ACTH-positive cells (Hernando et al, 2001), and modulate HPA axis activity in response to a variety of stressors (Roper et al, 2011) (see more discussion below).…”
Section: Avp Gene Expression In the Ppvnmentioning
confidence: 86%
“…In this experiment, rats were assigned to one of four treatment groups: (1) Acute cocaine withdrawal: n ¼ 8; (2) Saline control: n ¼ 6; (3) SSR149415 + Acute cocaine withdrawal: n ¼ 6; and (4) SSR149415: n ¼ 6. The SSR149415 dose chosen was based on previous studies, in which 1-30 mg/kg doses were observed to efficiently block HPA activation induced by a variety of stressors (Serradeil-Le Gal et al, 2002;Zhou et al, 2008b;Roper et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The first involves the hypothalamic magnocellular acting through its peripheral cognate V1a receptor [49,50] , a G-protein-coupled receptor signaling via phospholipase C [51][52] , is largely responsible for regulating water homeostasis and blood pressure [49,53] . The second system consists of parvocellular neurons within the PVN; these neurons produce both AVP and CRH peptide hormones [55] .…”
Section: Arginine Vasopressinmentioning
confidence: 99%
“…Acting through its cognate V1b receptor expressed on pituitary corticotrophs, AVP stimulates ACTH release [53,55,57] . The V1b receptor is largely responsible for regulating HPA-axis activity and responding to acute and chronic stressors in mammals [53,55] . …”
mentioning
confidence: 99%
“…V 1B antagonism in limbic brain regions may also contribute to ABT‐436 efficacy. In animal models of depression and anxiety, both HPA axis and limbic V 1B receptors contribute to effects demonstrated by V 1B antagonists (Roper, O'Carroll, Young, & Lolait, 2011). …”
Section: Introductionmentioning
confidence: 99%